RETRACTED ARTICLE: Upregulation of oxidative stress-responsive 1(OXSR1) predicts poor prognosis and promotes hepatocellular carcinoma progression. Issue 1 (1st January 2020) - Chen, Jianhui; Zhou, Jiangfan; Fu, Haotian; Ni, Xiaofeng; Shan, Yunfeng
Statement of Retraction: We, the authors, Editors and Publisher of the journal Bioengineered have retracted the following article: "Upregulation of oxidative stress-responsive 1(OXSR1) predicts poor prognosis and promotes hepatocellular carcinoma progression, " Jianhui Chen, Jiangfan Zhou, Haotian Fu, Xiaofeng Ni & Yufeng Shan. Bioengineered, Volume 11, 2020, Pages 958-971. Since publication, the authors raised the following concerns: Recently, in order to further explore the molecular mechanism of oxidative stress-responsive1(OXSR1) promoting the malignant progression of hepatocellular carcinoma (HCC), we repeated the previous research results. However, when we repeated the proliferation experiments, we found that compared with the result of the control group, there was no statistically significant difference in proliferation after knocking down OXSR1. Therefore, we continued to repeat the proliferation experiments several times. Unfortunately, the results of our repeated experiments did not show statistical differences. This indicates that the OXSR1 that the previous study proved to promote the proliferation of HCC is an unreliable result. Actually, OXSR1 does not promote the proliferation of HCC. Considering that in our previous study, OXSR1 promotes the proliferation of HCC is a very important conclusion, we decided to retract this article. The authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure the integrity of the scholarly record. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.